Production of High Viscosity Chitosan from Biologically Purified Chitin Isolated by Microbial Fermentation and Deproteinization - Ekkalak Ploydee; Saipin Chaiyanan (International Journal of Polymer Science)
The objective of this study was to produce high viscosity chitosan from shrimp chitin prepared by using a two-step biological treatment process: decalcification and deproteinization. Glucose was fermented with Lactobacillus pentosus L7 to lactic acid. At a pH of 3.9±0.1, the calcium carbonate of the shells was solubilized in 48 hours. The amounts of residual calcium in the form of ash (1.4±0.5%) and crude protein (23.2±2.5%) were further eliminated by the activity of proteolytic Bacillus thuringiensis SA. After decalcification and deproteinization of the shrimp shells, residual calcium and crude protein of shrimp chitin flakes were 1.7±0.4% and 3.8±1.3%, respectively. Chitin was deacetylated with 50% NaOH at 121°C for 5 hours. After deacetylation, the chitosan had residual calcium, crude protein content, and degree of acetylation of 1.6±0.6%, 0.4±0.3%, and 83.2±1.5%, respectively. The viscosity of chitosan prepared from chitin extracted by this two-step biological process was 1,007±14.7 mPa·s, whereas chitosan prepared from chemically processed chitin had a viscosity of 323±15.6   mPa·s, indicating that biologically purified chitin gave chitosan with a high quality.